Improving Knowledge and Skills Through ECEP and Integrated Service Posts for Stunting Prevention - Suparji Suparji; Teta Puji Rahayu; Tinuk Esti Handayani (Knowledge Dynamics, 2024)
Stunting is a serious health problem in Indonesia, affecting children's growth and development and the future of the younger generation. This community service aims to accompany early childhood education program (ECEP)and Integrated Service Post in implementing Early Stimulation, Detection and Intervention for Growth and Development of Children (ESDIGDC) services as an effort to prevent stunting. This activity involves training and mentoring for ECEP teachers and Integrated Service Post toddler cadres, focusing on understanding stunting, growth measurement techniques and appropriate early stimulation. The results of this program show a significant increase in participants' knowledge and skills regarding stunting and early detection. Parent participation in Integrated Service Post activities has also increased, with more children being checked regularly. In addition, several cases of stunting were detected early, allowing immediate intervention. The positive impact of this program is not only seen in stunting prevention, but also in increasing public awareness of the importance of monitoring children's growth and development and strengthening collaboration between ECEP and Integrated Service Post. Overall, this assistance has proven to be effective as a stunting prevention service intervention. It is hoped that this program can be adopted in other regions as a model in efforts to reduce stunting rates nationally.